2002
DOI: 10.1046/j.1432-1033.2002.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbaspirillum seropedicae signal transduction protein PII is structurally similar to the enteric GlnK

Abstract: PII-like proteins are signal transduction proteins found in bacteria, archaea and eukaryotes. They mediate a variety of cellular responses. A second PII-like protein, called GlnK, has been found in several organisms. In the diazotroph Herbaspirillum seropedicae, PII protein is involved in sensing nitrogen levels and controlling nitrogen fixation genes. In this work, the crystal structure of the unliganded H. seropedicae PII was solved by X-ray diffraction. H. seropedicae PII has a Gly residue, Gly108 preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The trimer formation is essentially similar to those of the GlnK (Xu et al, 1998) and GlnB structures (Cheah et al, 1994;Machado Benelli et al, 2002;Xu et al, 2003) and is consistent with the sedimentation equilibrium analysis results, which suggested that T. thermophilus GlnK behaves as a trimer in solution. In form Ib, the molecular surface area of molecule A is 7754 Å 2 , in which 31% (2380 Å 2 ) of the surface area facing molecules B and C is buried.…”
Section: Molecular Structuressupporting
confidence: 86%
See 1 more Smart Citation
“…The trimer formation is essentially similar to those of the GlnK (Xu et al, 1998) and GlnB structures (Cheah et al, 1994;Machado Benelli et al, 2002;Xu et al, 2003) and is consistent with the sedimentation equilibrium analysis results, which suggested that T. thermophilus GlnK behaves as a trimer in solution. In form Ib, the molecular surface area of molecule A is 7754 Å 2 , in which 31% (2380 Å 2 ) of the surface area facing molecules B and C is buried.…”
Section: Molecular Structuressupporting
confidence: 86%
“…The GlnB crystal structures from E. coli, Herbaspirillum seropedicae, and the cyanobacteria Synechococcus and Synechocystis, as well as the structure of GlnK from E. coli, have been reported (Cheah et al, 1994;Machado Benelli et al, 2002;Xu et al, 1998Xu et al, , 2003. The GlnB and GlnK structures are quite similar, and they share the Tloop, the B-loop, and the C-loop, which are assumed to be functionally important (Cheah et al, 1994;Xu et al, 1998).…”
mentioning
confidence: 99%
“…2 P II proteins sense carbon-related, nitrogen-related, and energy-related signals, and interact with diverse target proteins, most of which are involved in the regulation of nitrogen metabolism. A series of structures of P II proteins from bacteria, [3][4][5][6][7] archaea, 8 and plants 9 have been solved. All exist as trimers, with each subunit sharing a highly similar core structure of an antiparallel β-sheet and two α-helices at the lateral surface.…”
mentioning
confidence: 99%
“…The C-terminal residues extend out from the b4 strand to form a C-loop (Asp97 to Leu112) and has a 3 10 helix embedded within it between Gly108 and Ala111, consistent with other PII like protein structures. 16,24,[30][31][32][33][34][35] Structure of the ATP bound Mtb PII protein…”
Section: Structure Of the Mtb Apo Pii Proteinmentioning
confidence: 99%